Optimizing Marketing Strategies and Expenses in Medical Schemes, South Africa: Challenges and Solutions - Willie, Michael Mncedisi (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
Marketing strategies and expenses are crucial for businesses' success and growth in today's dynamic marketplace. This paper explores the importance of targeted marketing efforts aimed at specific audiences and delivering high-quality products at competitive prices. However, challenges persist in the medical scheme sector, where transparency and specificity in marketing expenses are lacking, hindering the assessment of their value to customers. Despite acknowledging various reasons for stagnant membership, including affordability and entry barriers, notable increases in marketing expenses within medical schemes have complicated the situation. Poor marketing strategies have been associated with organizational underperformance, particularly within medical schemes with disproportionately high marketing expenses, often leading to failure due to governance shortcomings. Moving forward, prioritizing the development of strong brand identities, clear messaging, and effective customer engagement strategies is essential for insurance companies to thrive in a competitive market. Additionally, future research should explore innovative approaches to optimize marketing investments, enhance consumer value, and increase membership in medical schemes.